N-Benzyl-9-isopropyl-9H-purin-6-amine - Gergela, David; Rouchal, Michal; Bartoš, Peter; Vícha, Robert (Acta crystallographica. Section E, Structure reports online, 2013)
The asymmetric unit of the title compound, C15H17N5, consists of two mol-ecules in which the dihedral angles between the best planes of the purine ring system (r.m.s. deviations = 0.0060 and 0.0190 Å) and the benzene ring are 89.21 (3) and 82.14 (4)°. The mol-ecules within the asymmetric unit are linked into dimers by pairs of N-H⋯N hydrogen bonds. Weak C-H⋯π contacts and π-π inter-actions [centroid-centroid = 3.3071 (1) Å] further connect the mol-ecules into a three-dimensional network.